Clinical characterization and epidemiology of 1560 cases of COVID-19 in Macapá/AP, extreme north of Brazil (Research, Society and Development, 2020)
The new coronavirus, called SARS-CoV-2, is a single-stranded RNA virus. The main mechanism of entry of the virus in the cells of the hosts is through the angiotensin-converting enzyme 2 (ACE-2) that acts as a receptor in the epithelial cells of the upper respiratory tract. The aim of this research was to describe the epidemiological profile of those affected by COVID-19 in the city of Macapá, Brazil, in addition to calculating the lethality rates by age group, sex and previous morbidity. A quantitative analysis was carried out based on confirmed cases of COVID-19 in the municipality of Macapá, with secondary data extracted from the database and aggregated information from the Municipal Health Department. The analysis of the epidemiological profile of those affected, the evolution and severity of COVID-19 is important to determine and adapt mitigation strategies and to allow the planning of actions and health care to combat SARS-CoV-2 in Macapá.